Altered expression patterns of circular RNAs between implantation sites and interimplantation sites in early pregnant mice. Issue 6 (28th October 2018) - Zhang, Shuang; Ding, Yubin; He, Junlin; Zhang, Juanjuan; Liu, Xueqing; Chen, Xuemei; Su, Yan; Wang, Yingxiong; Gao, Rufei
Abstract: Circular RNAs (circRNAs), a class of newly discovered endogenous noncoding RNAs, have been found to play important roles in regulating gene expression and participate in several biological processes. However, their specific roles in embryo implantation remain unclear. This study aims to investigate the roles of circRNAs in embryo implantation. In the current study, we screened the expression profiles of circRNAs between implantation sites and interimplantation sites in the endometrial tissue of early pregnant mice on Day 5 using microarray assay. Quantitative reverse transcription polymerase chain reaction (qRT‐PCR) of four dysregulated circRNAs was performed to validate the microarray results. Bioinformatics analyses, including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and circRNA–microRNA (miRNA)–messenger RNA (mRNA) negative correlation network analyses were performed. The microarray results showed 101 upregulated and 75 downregulated circRNAs (fold change [FC] ≥ 1.5 and p value < 0.05) at implantation sites compared with interimplantation sites. Four randomly selected circRNAs were successfully verified by qRT‐PCR. The GO and KEGG analyses revealed some meaningful terms. Moreover, based on circRNAs microarray data and the miRNA and mRNA high‐throughput data previously published by our groups, differently expressed circRNAs, miRNAs, and mRNAs were performed to conjoint analysis. Then circRNA–miRNA–mRNA negative correlation networks were constructed and 21 downregulated circRNAs, 14 upregulated miRNAs, and 79 downregulated mRNAs were involved in the networks. The findings of this study may provide a novel perspective on circRNAs and lay a foundation for future research into the potential roles of circRNAs in embryo implantation. Abstract : In the current study, we screened the expression profiles of circular RNAs (circRNAs) between implantation sites and interimplantation sites in the endometrial tissue of early pregnant mice on Day 5 using microarray assay, and bioinformatics analyses was performed. Our findings of this study may provide a novel perspective on circRNAs and lay a foundation for future research into the potential roles of circRNAs in embryo implantation.